Isoegomaketone exhibits potential as a new Mycobacterium abscessus inhibitor - Kim, Ho Won; Lee, Ji Won; Yu, A-Reum; Yoon, Hoe Sun; Kang, Minji; Lee, Byung Soo; Park, Hwan-Woo; Lee, Sung Ki; Whang, Jake; Kim, Jong-Seok (Frontiers in Microbiology, 2024)
Although the incidence of Mycobacterium abscessus infection has recently increased significantly, treatment is difficult because this bacterium is resistant to most anti-tuberculosis drugs. In particular, M. abscessus is often resistant to available macrolide antibiotics, so therapeutic options are extremely limited. Hence, there is a pressing demand to create effective drugs or therapeutic regimens for M. abscessus infections. The aim of the investigation was to assess the capability of isoegomaketone (iEMK) as a therapeutic option for treating M. abscessus infections. We determined the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of iEMK for both reference and clinically isolated M. abscessus strains. In addition to time-kill and biofilm formation assays, we evaluated iEMK's capability to inhibit M. abscessus growth in macrophages using an intracellular colony counting assay. iEMK inhibited the growth of reference and clinically isolated M. abscessus strains in macrophages and demonstrated effectiveness at lower concentrations against macrophage-infected M. abscessus than when used to treat the bacteria directly. Importantly, iEMK also exhibited anti-biofilm properties and the potential to mitigate macrolide-inducible resistance, underscoring its promise as a standalone or adjunctive therapeutic agent. Overall, our results suggest that further development of iEMK as a clinical drug candidate is promising for inhibiting M. abscessus growth, especially considering its dual action against both planktonic bacteria and biofilms.